2018
DOI: 10.1115/1.4038858
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation of Liquid Metal Turbulent Mixed Convection in a Vertical Concentric Annulus

Abstract: In the present study, turbulent forced and mixed convection heat transfer to a liquid metal flowing upwards in a concentric annulus is numerically investigated by means of large eddy simulation (LES). The inner-to-outer radius ratio is 0.5. The Reynolds number based on bulk velocity and hydraulic diameter is 8900, while the Prandtl number is set to a value of 0.026. A uniform and equal heat flux is applied on both walls. LES has been chosen to provide sufficiently accurate results for validating Reynolds-avera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Turbulent heat fluxes were modelled with a simple gradient diffusion hypothesis (Marocco et al, 2017), and the results showed that the turbulent Prandtl number (Pr t ) can be locally evaluated either with a correlation or by solving some additional transport equations. Furthermore, mixed large eddy simulation (LES) and direct numerical simulation (DNS) methods were also used to calculate the mixed convection of a liquid metal (Marocco and Garita, 2018), and the difference between the forced and assisted convection for the liquid metal was assessed at the same Reynolds number in detail. In addition, the flow and heat transfer characteristics of a liquid LBE in circular pipes were extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Turbulent heat fluxes were modelled with a simple gradient diffusion hypothesis (Marocco et al, 2017), and the results showed that the turbulent Prandtl number (Pr t ) can be locally evaluated either with a correlation or by solving some additional transport equations. Furthermore, mixed large eddy simulation (LES) and direct numerical simulation (DNS) methods were also used to calculate the mixed convection of a liquid metal (Marocco and Garita, 2018), and the difference between the forced and assisted convection for the liquid metal was assessed at the same Reynolds number in detail. In addition, the flow and heat transfer characteristics of a liquid LBE in circular pipes were extensively studied.…”
Section: Introductionmentioning
confidence: 99%